ASAS-ASAS HUKUM KELUARGA DALAM KOMPILASI HUKUM ISLAM (Membedah Pasal-pasal KHI) - Sulaeman, Budiman (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2011)
This article describes the problem attempts to dissect the articles in the Compilation of Islamic Law (KHI) in order to identify the principles of family law contained therein. From the identification results, it found the principles of family law, namely the principle of freedom, protection and preventive principles, the principle of monogamy, the principle of responsibility and justice, principles ijbari, bilateral principle, the principle of impartial justice, and the principle of legal certainty. Therefore, it can be affirmed that KHI had to cover the principles of family law. Except that, found some irregularities, inconsistencies and overlap, among others: (1) Lots of articles KHI is a duplication of the Law no. 1 of 1974, which should not speak in procedural areas, but focus on the substance, (2) In the use of the term, several articles in the KHI is less clear, or overlap and seem inconsistent in the use of words or phrases, such as words and qabla mitsaaqan ghaliizhan al-dukhuul, guardian of marriage, and marriage witnesses, (3) remove the authority of the guardian turns KHI mujbir to marry a woman without that persons consent, (4) KHI allow consent granted to a given power law.